PROBLEMS OF ESTABLISHING NATIONAL REFERENCE LEVEL FOR RADON - I. V. Yarmoshenko; A. D. Onishchenko; M. V. Zhukovsky (Радиационная гигиена)
Implementation of reference level conception for optimization of protection against radon in dwellings requires thorough consideration of a number of associated problems. With regard to both experience with regulation of indoor radon exposure in Russia and ICRP recommendations, Russian national reference level for radon should be expressed using annual radon concentration and set at level of 200 Bq/m3.